The Relationship between the Family Physician and Psychosomatic Medicine - Farzad Goli; Hamid Afshari; Ahmadreza Zamani; Amrollah Ebrahimi; Masoud Ferdosi (International Journal of Body, Mind and Culture, 2017)
Background: Organizing the health system around family medicine (FM) has been a productive approach for developed countries. The aim of this study, which was concurrent with the Iran Health Transform Plan (HTP) and the establishment of the family physician in Iran, was to discuss the sufficiency of a family physician training program for their roles and increase their competency. Methods: This descriptive study was conducted in the Psychosomatic Research Center affiliated to Isfahan University of Medical Science, Iran, with the assistance of the Iranian Institute of Higher Health (2015). An expert panel consisting of 6 individuals including specialists, trainers, and researchers in FM and psychosomatic medicine was held for this purpose. Using the World Organization of Family Doctors‎ (WONCA) website for the definition of a family physician, the curriculum developed by the Ministry of Health and Medical Education was studied. Data were summarized in one table. Results: The current FM curriculum, with this content and method, does not seem to be capable of enabling physicians to perform their multidisciplinary roles. it still has a reductionist approach and disease orientation instead of a clinical reasoning method and systematic viewpoint. The psychosomatic approach is applicable at all prevention levels and in all diseases‎, since it is basically designed for this longitudinal (between all preventive levels) and horizontal (bio-physical–social-spiritual intervention) integration. Conclusion: Psychosomatic medicine, not as a biomedical specialty, but rather as a systems thinking model in health, had a rapid rise during previous decades. Now, its services have been integrated into all medical fields. This means that it should be adopted in the core of health care services (i.e., the family physician position) before other sections. This would help the implementation of this approach in the health system, and the reduction of patients' pain and uncertainty and improvement of their health. Thus, psychosomatic approaches for family physicians only emphasize on some of their fundamental acts.